2020
DOI: 10.3390/cancers12123839
|View full text |Cite
|
Sign up to set email alerts
|

3′RNA Sequencing Accurately Classifies Formalin-Fixed Paraffin-Embedded Uterine Leiomyomas

Abstract: Uterine leiomyomas are benign smooth muscle tumors occurring in 70% of women of reproductive age. The majority of leiomyomas harbor one of three well-established genetic changes: a hotspot mutation in MED12, overexpression of HMGA2, or biallelic loss of FH. The majority of studies have classified leiomyomas by complex and costly methods, such as whole-genome sequencing, or by combining multiple traditional methods, such as immunohistochemistry and Sanger sequencing. The type of specimens and the amount of reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…We acknowledge that the archival age of our samples affects their RNA quality and therefore reduces the power to detect differential gene expression. We, however, used a method successfully applied on archival samples in several recent studies to be able to study our unique cohort with extended follow-up times [34,35]. Therefore, we believe that our results are still valid and in line with previous findings; a subset of AGCT patients gain secondary mutations, but they do not explain the diverse clinical behavior of this disease, and the FOXL2 C402G mutation remains the main driver of this disease [36].…”
Section: Discussionsupporting
confidence: 73%
“…We acknowledge that the archival age of our samples affects their RNA quality and therefore reduces the power to detect differential gene expression. We, however, used a method successfully applied on archival samples in several recent studies to be able to study our unique cohort with extended follow-up times [34,35]. Therefore, we believe that our results are still valid and in line with previous findings; a subset of AGCT patients gain secondary mutations, but they do not explain the diverse clinical behavior of this disease, and the FOXL2 C402G mutation remains the main driver of this disease [36].…”
Section: Discussionsupporting
confidence: 73%
“…To explore the gene expression pattern of AKR1B10hi leiomyomas, we performed 3′RNA sequencing with thirteen AKR1B10hi leiomyomas and seven corresponding myometrium samples. We analyzed these samples together with a previously published dataset of 44 leiomyomas [ 16 ]. Principal component analysis revealed that the AKR1B10hi samples clustered separately from the other three established leiomyoma subtypes, but close to leiomyomas of the FH subtype (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3′RNA sequencing was performed with 13 leiomyomas and 7 corresponding myometrium samples as previously described [ 16 ]. These 20 samples were analyzed together with a previously published dataset of 44 leiomyomas (13 leiomyomas with a MED12 mutation, 15 with significant HMGA2 overexpression, and 16 with FH- deficiency) and 5 myometrium samples [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However these techniques have not emerged yet as optimal for prognostic determination in ACC. The 3' RNA sequencing recently emerged as an opportunity to study transcriptome signatures from FFPE material, as reported for several tumor types [37][38][39] . This technique was applied to samples from operated patients.…”
Section: Discussionmentioning
confidence: 99%